Intra-Functional Linkages and Employee Commitment in Work Organizations: A Survey of Bayelsa State Civil Service - Akpotu, Christopher; Rachel, Konyefa (American Journal of Social Sciences and Humanities, 2019)
There is emerging shift form in conceptual and theoretical focus on what workplace dimension relates with employee commitment. While it is hitherto posited that behavioural concerns are channeled by social relational action at work, the structural dynamics in terms of how they create intra functional relationship towards goals needs to be explored therefore this study scientifically examines the empirical relationship between intra-functional linkages and employee commitment. The study which was conducted within the Bayelsa State Civil Service used the questionnaire marked INFECQ to generate data primarily from a sample of 236 respondents that were obtained through a proportionate stratified random sampling. The data generated were descriptively and inferentially analyzed. The standardized β value of 0.537 & .256 from the multiple regression indicates that team work and collaboration has significant relationship with employee commitment in the civil service respectively. It shows that teamwork has strong impact than collaboration and brainstorming. It was concluded that intra-functional linkage creates a stimulating work setting that instigates employee commitment therefore, it was recommended amongst others that structural flexibility should be ensured as it helps to integrate work units where information can be commonly shared for goal.